2010
DOI: 10.1016/j.jep.2010.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of plant extracts in traditional medicine of the Brazilian Cerrado against protozoans and yeasts

Abstract: The active extracts for protozoans and human pathogenic yeasts are considered promising to continue the search for the identification and development of leading compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 37 publications
1
25
0
6
Order By: Relevance
“…As observed in the present study, several species of genus Calophyllum showed inhibitory potency against S. aureus [12,13] . The antimicrobial activity of C. inophyllum sourced from other locales are already acknowledged by many authors [14][15][16] .…”
Section: Discussionsupporting
confidence: 82%
“…As observed in the present study, several species of genus Calophyllum showed inhibitory potency against S. aureus [12,13] . The antimicrobial activity of C. inophyllum sourced from other locales are already acknowledged by many authors [14][15][16] .…”
Section: Discussionsupporting
confidence: 82%
“…A coumarin was isolated from this extract and its derivatives showed significant activity against L. amazonensis, with IC 50 between 0.6 and 34.0 µg/mL (Brenzan et al, 2007;Brenzan et al, 2008). On other hand, the extract from roots of C. brasiliense was active against L. chagasi and Plasmodium falciparum, with an IC 50 of 6.7 and 27.6 g/mL, respectively (Albernaz et al, 2010). Other study reported the purification of three xanthones from heartwood, which exhibited activity against epimastigote forms of Trypanosoma cruzi (Abe et al, 2004).…”
Section: Resultsmentioning
confidence: 95%
“…Eugenol was found to completely inhibit the bacteria at a concentration of double the MIC (4 mg/mL) in about 1 h of incubation at acidic pH MIC of eugenol: 2 mg/ mL Ali et al (2005) Geranium DOI: 10.3109/13880209.2014.952837 ailments including rheumatism, varicose, hemorrhoids, and chronic ulcers (Sartori et al, 1999). The activity against protozoans and human pathogenic yeasts (Albernaz et al, 2010), cancer chemopreventive properties, antifungal (RuizMarcial et al, 2007;Suffredini et al, 2007), antisecretory, antiulcer (Sartori et al, 1999), gastroprotective (ReyesChilpa et al, 2006), and analgesic activities (da Silva et al, 2001) have been reported in different studies. Souza et al (2009) evaluated the effects of various extracts of C. brasiliense stem bark, against H. pylori in vivo and in vitro.…”
Section: Cocculus Hirsutusmentioning
confidence: 99%